Respuesta :
Answer:
P1 = ρ g h1
v1 = √(2g(h2 - h1)/(1 - γ^2))
Explanation:
a)
P1 = ρ g h1
b)
P2 = ρ g h2
P2 - P1 = 0.5 ρ (v1^2 - v2^2)
ρ g h2 - ρ g h1 = 0.5 ρ (v1^2 - v2^2)
g h2 - g h1 = 0.5 (v1^2 - v2^2)
2 g (h2 - h1) = v1^2 - v2^2
v1 A1 = v2 A2 >>>>> v2=v1(A1/A2)
2 g (h2 - h1) = v1^2 - v1^2 (A1/A2)^2
2 g (h2 - h1) = v1^2 (1 - (A1/A2)^2)
2 g (h2 - h1) = v1^2 (1 - γ^2)
v1 = √(2g(h2 - h1)/(1 - γ^2))
The gauge pressure at the bottom of tube 1 is;
P1 = ρgh1
The velocity at the bottom of tube 1 is;
v1 = √(2g(h2 - h1))/(1 - γ²)
Formula for gauge pressure is;
P = ρgh
Where;
ρ is density
g is acceleration due to gravity
h is height
Thus;
P1 = ρgh1
P2 = ρgh2
Now, from bernoulli equation, we know that;
P2 - P1 = ½ρ((v_1)² - (v_2)²)
Thus, Plugging in the relevant values of P1 and P2 gives;
ρg(h2 - h1) = ½ρ((v_1)² - (v_2)²)
ρ will cancel out to give;
2g(h2 - h1) = ((v_1)² - (v_2)²)
We also know from bernoulli equation that;
V1A1 = V2A2.
Since we want to find v1, let us make V1 the subject of the formula;
v_2 = v1(A1/A2)
Thus;
2g(h2 - h1) = ((v1)² - v1²(A1/A2)²)
Factorizing gives;
2g(h2 - h1) = v1²(1 - (A1/A2)²)
A1/A2 can be expressed as γ. Thus;
2g(h2 - h1) = v1²(1 - γ²)
v1 = √(2g(h2 - h1))/(1 - γ²)
Read more at; https://brainly.com/question/15396422